Practice-Based Research as Reciprocal Protocol: Constellations of Care in The Seventh Fire - Cooke Ravensbergen, Lisa (Performance Matters, 2023)
The Seventh Fire is an immersive audio performance that sources traditional, oral Anishinaabe stories and societal roles as a way to evoke ceremony in the everyday. I use the experience of creating this new form and premiering this work as an opportunity to reflect on principles of reciprocity that underscore and infuse any practice-based inquiry, as well as propose some necessary structures of care to support these principles.